SCIENTOMETRIC DIMENSIONS OF NUCLEAR SCIENCE AND TECHNOLOGY RESEARCH IN INDIA: A STUDY BASED ON INIS (1970-2002) DATABASE - Kademani, B. S.; Kumar, Vijai; Sagar, Anil; Kumar, Anil (Malaysian Journal of Library and Information Science, 2006)
This paper analyses quantitatively the growth and development of Nuclear Science and Technology research in India in terms of publication output as reflected in International Nuclear Information System (INIS) (1970-2002) database. During 1970-2002 a total of 55313 papers were published by the Indian Nuclear scientists in various domains: Physics (23033), Chemistry (16368), Life and Environmental Sciences (7203), Engineering and Technology (6960), Other Aspects of Nuclear and Non Nuclear Energy (981) and Isotopes and Radiation Application (768). Year-wise growth of publications and input of records to INIS database by India and other countries were analysed. The total number of records input to INIS database by India was 30356 (54.88%) and by other countries and international organizations 24957 (45.12%). The average number of papers published per year was 1676.15. The average Indian contribution to the world literature was 2.25%. Authorship and collaboration trend was towards multi-authored papers. Intensive international collaboration was found during the period and bilateral collaboration accounted for 80.06% of the total collaborative papers. More than 99% of publications were published in English. More than 60% of publications were published in journals. Most preferred journals by the scientists were Pramana 1327 (3.95%), Indian Journal of Pure and Applied Physics 1104 (3.29%), Physical Review-D 925 (2.75%), Journal of the Indian Chemical Society 783 (2.33%) and Indian Journal of Chemistry-A 734 (2.19%). High frequency Indexer Assigned Descriptors were: Gamma-radiation (4076), Temperature–dependence (3220), Experimental – data (2749), Radiation – doses (2306) and India (2000).